"It Matters What I Think, Not What You Say": Scientific Evidence for a Medical Error Disclosure Competence (MEDC) Model. Issue 8 (December 2021) - Hannawa, Annegret F.; Frankel, Richard M.
Abstract : Objective: This study sought to validate the ability of a "Medical Error Disclosure Competence" (MEDC) model to predict the effects of physicians' communication skills on error disclosure outcomes in a simulated context. Method: A random sample of 721 respondents was assigned to 16 experimental disclosure conditions that tested the MEDC model's constructs across 2 severity conditions (i.e., minor error and sentinel event). Results: Severity did not affect survey respondents' perceptions of the physician's disclosure style. Respondents who viewed the nonverbally skilled disclosure perceived the disclosure as more adequate compared to respondents in the "low nonverbal skill" disclosure condition. Interpersonal adaptability did not affect respondents' adequacy ratings. Consistent with the MEDC model, those who viewed the physician's error disclosure as inadequate indicated that they would be more prone to engage in relational distancing behaviors, while those who rated the disclosure as adequate were more likely to reinvest into their relationship with their physician. These respondents also had higher resilience scores. In the context of a sentinel event, perceived adequacy significantly predicted endorsing legal redress or remedies (e.g., lawsuit). Verbal apology (e.g., "I'm sorry, " "I apologize") did not predict any significant variance in the model beyond the physician's nonverbal skill. Conclusion: In a simulated disclosure setting, physicians' communicative skills—particularly effective nonverbal communication during a disclosure—trigger outcomes that affect the patient, the physician, and the provider-patient relationship. Findings from this study suggest that MEDC guidelines may be helpful in reducing financial and reputational risks to individual providers and institutions, particularly in the context of a sentinel event.